Effect of a Mindfulness Training Program on the Impulsivity and Aggression Levels of Adolescents with Behavioral Problems in the Classroom - Franco, Clemente; Amutio, Alberto; López-González, Luís; Oriol, Xavier; Martínez-Taboada , Cristina (Frontiers in Psychology, 2016)
Objective: The aim of the present study was to analyze the effects of a mindfulness training psycho-educative program on impulsivity and aggression levels in a sample of high school students. Methods: A randomized controlled trial with pretest-posttest measurements was applied to an experimental group and a control group (waiting list). The Barratt Impulsivity Scale (BIS-11) (Barratt, 1995) and the Aggression Questionnaire (AQ) (Buss and Perry, 1992) were used. Results: Statistical analyses showed a significant decrease in the levels of impulsivity and aggressiveness in the experimental group compared with the control group. These results have important implications for improving the level of academic engagement and self-efficacy of students and for reducing school failure. Conclusion: This is one of the first studies showing the effectiveness of mindfulness training at reducing impulsive and aggressive behaviors in the classroom. The efficacy of mindfulness-based programs is emphasized.